PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK MOOD, UNDERSTAND, RECALL, DIGEST, EXPAND AND REVIEW (MURDER) DENGAN PEMBELAJARAN KONVENSIONAL PADA MATA PELAJARAN EKONOMI SISWA KELAS X SMA N 14 PADANG - Yusnia, Reni; Hia, S.Pd, MM, Yulna Dewita; Sumarni, M.Pd, Sumarni, M.Pd (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This study aimed to analyze the differences in student learning outcomes using the model of cooperative learning with conventional learning techniques MURDER on economic subjects class X SMA N 14 Padang . This research is an experimental study . This study population adalaah whole class X students enrolled in the school year 2013/2014 . Sampling with purposive sampling technique in order to obtain a sample of the class as a class experiment X4 and X3 as grade control class . Testertulis instrument used is in the form of an objective matter . Data were analyzed by descriptive and inductive analysis through z test by first doing a test for normality and homogeneity of variance of the two samples . Based on the analysis of data obtained an average value of 76.12 experimental class and control class average of 71.48 . From the analysis of the data found zhitung value = 2.0714 is greater than the value ztabel = 1.960 which means that the hypothesis is accepted at significance level Î± = 0.05 . This suggests that there are significant differences between the results of student learning using cooperative learning techniques Mood , Understand , Recall , Digest , Expand and Review ( MURDER ) with conventional learning . That is economics student learning outcomes using the model of cooperative learning techniques Mood , Understand , Recall , Digest , Expand and Review ( MURDER ) , better economics student learning outcomes learning process using conventional learning on economic subjects class X SMA N 14 Padang . From the results of this study are expected to provide an outlet for a low issue of student learning outcomes , especially in the economic subjects . uintuk suggested to teachers to consider cooperative learning model MURDER techniques to improve student learning outcomes .